Pengaruh Brand Image, Trust Dan Perilaku Konsumen Terhadap Keputusan Pembelian Produk Skincare Benings di Kota Batam - Wulandari, Nurianda; Evyanto, Winda (YUME : Journal of Management, 2025)
This research was conducted to determine the influence of Brand Image, Trust, and Consument Behavior on the Purchasing Decision of Benings Skincare Products in Batam City. The sample for this study consisted of 102 respondents, using purposive sampling method, with data collected through the distribution of questionnaires. The analysis was performed using SPSS version 26, which included data quality tests, classical assumption tests, effect tests, and hypothesis tests. The method applied in this research used multiple linear regression analysis. The results indicate that the brand image and consument behavior variables have a positive and significant effect, both partially and simultaneously, on the purchasing decision of Benings Skincare products in Batam City. In contrast, the trust variable does not have a positive and significant effect on the purchasing decision of Benings Skincare products, both partially and simultaneously. This research can be used to develop Benings Skincare products in Batam City in the future. Keywords: Brand Image, Trust, Consument Behavior, Purchasing Decision